A system approach to simulation of individual food products - A. B. Lisitsyn; I. M. Chernukha; M. A. Nikitina (Теория и практика переработки мяса)
There is no doubt that the further development in the field of nutrition is linked with personalization. Nutrition management with account for metabolism plays a key role in health strengthening and prevention of human diseases. The paper gives a review of studies associated with personalized nutrition. Personalized nutrition is inextricably linked with personalized food products. At present, however, mass production of personalized food products for individuals or small groups of people is unfeasible. The devel‑ opment of personalized food products requires both time and labor input, as well as multidisciplinary and profound knowledge in a wide spectrum of areas associated with biology, medicine, nutrition and food systems. Among the most important characteristics of modern science is the study of complex and super-complex organized objects such as the food system. These objects were studied previously but by the way of significant simplification of their structure. Investigation of objects with all variety and complexity of their organization requires not only new scientific ideas but also a new conceptual framework, new research methodology, new approaches to simulation of both products and physiological processes. In this study, the authors made an attempt to bring the theoretical view on an individual product closer to the complex task solution using the method of mathematical physiology. The intuitive conceptual model for a process of food design is shown with regard to the “health passport” of an individual, disease risk and gastrointestinal (GI) tract status. The differential equations of the concentration dynamics of protein, denatured protein and peptides in the human stomach are presented. The differential equations that describe the process of protein assimilation in the human stomach were solved in the simulation environment Simplex 3. The presented fragments of model realization show the pos‑ sibility of virtual study on an effect of different indicators of the food nutritional value on the rate of digestion and the process of cleavage of complex components (proteins, fats and carbohydrates) to mono-structural elements depending on different state and influence factors.